Designing a computational thinking module for STEM teachers: a design and development approach - Jaya, Sanura; Zaharudin, Rozniza; Amar Singh, Parvinder Singh s/o (Institute of Advanced Engineering and Science, 2025)
This study investigates the necessity of computational thinking (CT) skills integration among science, technology, engineering, and mathematics (STEM) secondary school teachers, focusing on the development of the McodE pedagogical module for the topic of heat in solar still projects. Utilizing a design and development research (DDR) approach, the research aimed to design and develop a CT module tailored to enhance teachers’ pedagogical strategies in solar still project. The case study was employed with 32 STEM secondary school teachers, through purposive sampling participated in the study based on their experience in integrating technology into pedagogy. A pre-test and post-test design was employed during a two-day workshop to assess the participants’ CT skills before and after the intervention. An additional open-ended interview was conducted among three teachers to support the quantitative data. The results revealed significant improvements in various aspects of CT application. The findings demonstrated substantial increases in teachers’ abilities to integrate CT into their teaching practices. The mean for pre-test score was 43.25, which significantly increased to 67.37 in the post-test, indicating a marked enhancement in CT skills. The t-test statistics for the pre-test (t=31.04, df=31, p<.001) and post-test (t=49.94, df=31, p<.001) confirmed a highly significant differences between the pre-test and post-test scores. The open-ended interview also showed the strong interest and necessity of the CT module among the respondents. The study concludes that there is a critical need for CT module among STEM teachers to better prepare students for the demands of modern STEM education.